When do we really need coronary calcium scoring prior to contrast-enhanced coronary computed tomography angiography?: analysis by age, gender and coronary risk factors - Gitsioudis, Gitsios; Hosch, Waldemar P.; Iwan, Johannes; Voß, Andreas; Atsiatorme, Edem; Hofmann, Nina P.; Buß, Sebastian Johannes; Siebert, Stefan; Kauczor, Hans-Ulrich; Giannitsis, Evangelos; Katus, Hugo; Korosoglou, Grigorios (PLOS ONE, 2014)
To investigate the value of coronary calcium scoring (CCS) as a filter scan prior to coronary computed tomography angiography (CCTA).